Matrix and Backstage: Cellular Substrates for Viral Vaccines - Jordan, Ingo (MDPI, 2014)
Vaccines are complex products that are manufactured in highly dynamic processes. Cellular substrates are one critical component that can have an enormous impact on reactogenicity of the final preparation, level of attenuation of a live virus, yield of infectious units or antigens, and cost per vaccine dose. Such parameters contribute to feasibility and affordability of vaccine programs both in industrialized countries and developing regions. This review summarizes the diversity of cellular substrates for propagation of viral vaccines from primary tissue explants and embryonated chicken eggs to designed continuous cell lines of human and avian origin.